SINKRONISASI PERLINDUNGAN HUKUM TERHADAP PENYANDANG DISABILITAS TUNA GRAHITA SEBAGAI SAKSI KORBAN DALAM PROSES PERADILAN PIDANA - Novianti, Dian; Michael, Tomy (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Protection of clear legal rights for persons with intellectual disabilities is promulgated in Law No. 8/ 2016. However, these legal provisions face disharmony because they are out of sync with the laws and regulations that govern criminal justice in the matter of being a victim-witness. This conflict between law and related legislation raises the most important ambiguity in matters of law enforcement. therefore, must try horizontal sync. Legal requirements regarding the standard procedure for determining witnesses for a variety of disabilities, the obligation to assist mentally retarded people linked to legal expertise and accessibility for persons with disabilities in court of law. The government needs as soon as possible to draft a government regulation as the implementing provision of Law No. 8/ 2016, so that there is clarity and legal certainty, especially for law enforcers and people with intellectual disabilities